Biotechnological production, characterization and in vitro antitumor activity of polysaccharides from a native strain of Lentinus crinitus - López Legarda, Xiomara; Arboleda Echavarría, Carolina; Parra Saldívar, Roberto; Rostro Alanis, Magdalena; Alzate, Juan F.; Villa Pulgarín, Janny Alexander; Segura Sánchez, Freimar (Elsevier BV, 2020)
This work deals with the submerged cultivation, extraction and antitumor activity of polysaccharides from Lentinus crinitus. The fungus was isolated from a tropical forest (Antioquia, Colombia), cultivated in laboratory conditions, and classified by classical and molecular taxonomy. Then, it was cultivated in a bioreactor of 5 L using a ligninolytic residue as substrate. The fermentation conditions were 30 ± 1 °C, pH 4.5, 300 rpm and 1.5 vvm for 4 days. The yields of fermentation were 20 g/L of biomass. After extraction, 0.65 g/L of water-soluble exopolysaccharide (LEPS) and 3.3 mg/100 g of water-soluble intrapolysaccharide (LIPS) were obtained. In each extract total carbohydrate, glucans and protein contents were determined. Also, scanning electron microscopy (SEM), Fourier transform infrared (FTIR), X-ray diffractometry (XRD), high performance liquid chromatography with refraction index detection (HPLC-RI) and high performance gel permeation chromatography (HPGPC) analysis for characterization were performed. The antitumor activity was evaluated and polysaccharides not only showed anti-proliferative activity in breast cancer cells but also they activate J774 macrophages as evidenced by the increase of nitric oxide and tumor necrosis factor-α (inducers of tumor cell apoptosis). Our findings suggest that polysaccharides can activate macrophages to release nitric oxide (NO) and tumor necrosis factor alpha (TNF-α), which directly blocks cancer cell growth. These findings enhance our knowledge about new sources of fungal metabolites that serve as coadjuvant, cheap and less harmful alternatives to cancer treatment.
Keywords: Lentinus Crinitus; Polisaccharides; Submerged Cultivation; Antitumor; Biotechnology; Beta Glucans; Oncología; Tumores; Cáncer